2013
DOI: 10.1097/mib.0b013e31828028e8
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of the “A Disintegrin And Metalloprotease” 19 (ADAM19), a Sheddase for TNF-α in the Mucosa of Patients with Inflammatory Bowel Diseases

Abstract: These findings suggest the existence of a positive feedback mechanism involving cytokines and ADAM19 that can amplify cytokine production in IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
(40 reference statements)
2
20
0
Order By: Relevance
“…Several studies have shown that TNF levels are upregulated in human IBD (10, 26). Having demonstrated TNF-regulation of NPY promoter in vitro , we next assessed if administration of TNF inhibitors can attenuate NPY expression during experimental colitis in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that TNF levels are upregulated in human IBD (10, 26). Having demonstrated TNF-regulation of NPY promoter in vitro , we next assessed if administration of TNF inhibitors can attenuate NPY expression during experimental colitis in mice.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that Adam17 expression is upregulated in the intestinal mucosa of patients with IBD and in several mouse models of experimental colitis (99103). Adam19 expression is also elevated in IBD (104). Apart from these reports, however, limited information exists on the role of these or other ADAMs in intestinal inflammation.…”
Section: Adams Intestinal Injury and Inflammatory Bowel Diseasementioning
confidence: 99%
“…Treatment of TIMP3-deficient colonic epithelial cell line HT29-C1.16E with TIMP3, an inhibitor of ADAM17 activity, decreased TNF shedding and sensitized the cells to TNF-mediated epithelial hyperpermeability due to the downregulation of zonula occludens-1 proteins [64]. Other reports showed that IBD patients had also elevated mucosal expression of another TNF sheddase, metalloprotease ADAM19, localized mainly in epithelial cells [68], whereas a mouse study demonstrated that shedding of TNF can be mediated also by matrix metalloproteinase 13 (MMP13) [69]. …”
Section: Tnfmentioning
confidence: 99%